Effect of Modified Form of Porcelanite Rocks to Remove Remazol Brilliant Blue Dye From Aqueous Solution and Adsorption Isotherm Model Studies - Noor A. Al-Khazali (Journal of Global Pharma Technology, 2016)
The adsorption of Remazol Brilliant Blue dye from aqueous solutions by using (Porcelanite- Melamine-Urea) (PMUC) as an adsorbent .The characterization of (PMUC) was done by using FTIR spectroscopy, X-ray diffraction (XRD), (SEM) scanning electron microscopy and (AFM) Atomic force microscopy. Different experimental data such as contact time, pH, adsorbent dosage and ionic strength were studied. The equilibrium experimental data were analyzed by Langmuir, Freundlich and Temkin isotherm models. Thermodynamic parameters such as change in free energy (ΔG°), enthalpy (ΔH°), and entropy (ΔS°) were also determined.Keywords: Adsorption, Porcelanite rocks, Remazol Brilliant Blue, Isotherms, Langmuir, Freundlich, Temkin.